The Neurobiological Pathogenesis of Poststroke Depression - Chao Feng; Min Fang; Xue-Yuan Liu (The Scientific World Journal)
Poststroke depression (PSD) is an important consequence after stroke, with negative impact on stroke outcome. The pathogenesis of PSD is complicated, with some special neurobiological mechanism, which mainly involves neuroanatomical, neuron, and biochemical factors and neurogenesis which interact in complex ways. Abundant studies suggested that large lesions in critical areas such as left frontal lobe and basal ganglia or accumulation of silent cerebral lesions might interrupt the pathways of monoamines or relevant pathways of mood control, thus leading to depression. Activation of immune system after stroke produces more cytokines which increase glutamate excitotoxicity, results in more cell deaths of critical areas and enlargement of infarctions, and, together with hypercortisolism induced by stress or inflammation after stroke which could decrease intracellular serotonin transporters, might be the key biochemical change of PSD. The interaction among cytokines, glucocorticoid, and neurotrophin results in the decrease of hippocampal neurogenesis which has been proved to be important for mood control and pharmaceutical effect of selective serotonin reuptake inhibitors and might be another promising pathway to understand the pathogenesis of PSD. In order to reduce the prevalence of PSD and improve the outcome of stroke, more relevant studies are still required to clarify the pathogenesis of PSD.